The examination of the effectiveness of metacognitive therapy on emotion regulation, stress level, and despair among women with postpartum depression - Farzaneh, Fahimeh; Afzali, Maryam (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to determine the effectiveness of metacognitive therapy on emotion regulation, level of stress, and despair among women with postpartum depression. Methods: The research method was experimental with a pretest-posttest design, a control group, and follow-up. The statistical population included all patients with postpartum depression referred to general health centers in Fardis city. And 30 patients with postpartum depression were selected based on the convenience sampling method and assigned to the experimental group (n = 15) and control group (n = 15). The Metacognitive Therapy of Wells (2000) was performed in 10 sessions of each 90-minute. The data collection tools included the disappointment scale of Beck (1974), the emotion regulation questionnaire of Garnefski et al. (2001), and the depression anxiety stress scale of Lavibond and Lavibond (1995). The data analysis method included descriptive and inferential statistical methods, repeated measures analysis of variance through SPSS-19 software. Results: The findings indicated the impact of metacognitive therapy on stress score (F = 4.62, P = 0.040), despair score (F = 61.94, P = 0.001) and on emotion regulation score (F = 14.65, P = 0.001). And the results were stable in the follow-up stage. Conclusions: The research findings indicate that metacognitive therapy can be used by psychologists and counselors as an effective treatment for emotion regulation, level of stress, and despair in patients with depression.